Exergy optimization for an endoreversible cogeneration cycle - Sahin, B; Kodal, A; Ekmekci, I; Yilmaz, T (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
Exergy optimization has been carried out for an endoreversible cogeneration cycle using finite-time thermodynamics. The optimum values of the design parameters of the cogeneration cycle at maximum exergy output were determined. Our model is more general than the endoreversible power cycle found in the literature. The effects of design parameters on exergetic performance are investigated and the results discussed. (C) 1997 Elsevier Science Ltd.
Keywords: Thermodynamics; Energy & Fuels